Microbiological Quality and Presence of Foodborne Pathogens in Raw and Extruded Canine Diets and Canine Fecal Samples - Solís, Doina; Toro, Magaly; Navarrete, Paola; Faúndez, Patricio; Reyes-Jara, Angélica (Frontiers in Veterinary Science, 2022)
Pet food can be a source of microbiological hazards that might affect companion animals and owners. Even though owners usually rely on conventional pet diets, such as extruded diets, new feeding practices, such as raw meat-based diets (RMBDs), have grown. RMBDs’ benefits are still scientifically uncertain, while its risks have been documented. The use of canine RMBDs might increase the exposure to zoonotic pathogens, such as Salmonella spp., Listeria monocytogenes, Campylobacter spp., among others. Identifying pathogen prevalence in canine food and pets is required to contribute to public health measures. The aims of this study were: 1) to compare the microbiological quality of RMBDs and extruded diets 2) to identify and compare the prevalence of Salmonella spp., Campylobacter jejuni, and L. monocytogenes from raw and extruded canine diets and canine fecal samples, and 3) to characterize pet owners according to the diet chosen to be used on their pets, their motivations for using RMBDs, and their knowledge about benefits and risks related to this feeding practice. Conventional and molecular microbiological methods were used to identify pathogen presence from food and fecal samples, while pulsed-field gel electrophoresis (PFGE) was performed to evaluate the clonal relationship between isolates. Aerobic plate counts for RMBDs were higher than those detected for extruded diets. Salmonella spp. and L. monocytogenes were isolated from 35.7 % (15/42) RMBDs, while Salmonella spp., C. jejuni, and L. monocytogenes from 33.3 % (11/33) fecal samples from RMBD-fed dogs. From the RMBD samples positive to Salmonella spp., chicken was the main meat ingredient composing the diets. PFGE analysis confirmed a genetic association between Salmonella spp. isolates from fecal and raw food samples from the same household. We did not detect pathogens from extruded food samples or feces from extruded-fed dogs. Using a survey, we identified dog owners’ unawareness and/or underestimation of risks related to RMBDs. We demonstrated that canine raw pet food might be a source of zoonotic foodborne pathogens that represent a health risk for both humans and pets. While clinical findings caused by the mentioned pathogens vary among pets, the zoonotic potential implies a significant concern.